Guidance for the Investment of Temporary Resources to Generate Income to Contribute to PRG, PRG-HIPC, and CCR Trusts. (Policy Papers; Policy Paper ;, 2017)
On July 28, 2017, the Executive Board approved the following decision on the Investment of Temporary Resources to Generate Income to Contribute to PRG, PRG-HIPC, and CCR Trusts. This decision references the Guidelines for Investing PRG, PRG-HIPC, and CCR Trust Assets, which were adopted by the Executive Board on March 22, 2017. These Guidelines are also available to the public.